THE EFFECT OF DISCOVERY LEARNING MODEL ON NARRATIVE WRITING SKILLS IN GRADE V ELEMENTARY SCHOOL - Mahpudin Mahpudin; Dudu Suhandi Saputra; Budi Febriyanto; I'malul Ikhsan; De'tiar Purnama; Agus Rofi'i (Jurnal Cakrawala Pendas, 2024)
This study was motivated by the low writing skills of grade V students. The purpose of this study was to determine the effect of the Discovery Learning model on the writing skills of elementary school students. The research method used was quasi-experimental. The sample in this study were grade VA and grade VB students of SDN Munjul II in the 2024/2025 academic year with research subjects of 20 experimental class students and 20 control class students determined through purposive sampling. The data collection technique in this study was through a narrative writing test. The results of the analysis showed that the results of the independent sample t-test for the experimental class and the control class showed a significance value (2-tailed) of 0.048, which is less than 0.05 (sig <0.05) so that Ho was rejected and Ha was accepted. This means that there is a significant difference in students' writing skills between the experimental class given the Discovery Learning model treatment and the control class given the Direct Instruction model treatment.